Potential of Lasers in the Realm of Aesthetic Dentistry: A Narrative Review - Meghana, Ivaturi Sri Sai; Bhat, Amitha Ramesh; Bhandary, Rahul; Thomas, Biju (Journal of Health and Allied Sciences NU, 2022)
In contemporary dental practice, patients' interests are taken into account in terms of function and appearance. The importance in everyday circumstances, current advertising, and the media in general highlight their effect on an attractive appearance. Many academics in the field of dental aesthetics have stated equivocally that when examining the impact of tooth appearance necessitates a multidisciplinary approach. Laser technology in cosmetic dentistry is in its early stages of development and has a lot of potential in the future. Also, with expanding use of lasers in clinical dentistry, treatment planning and prognosis will see a significant improvement in the future. The introduction of this technology has turned dentistry into a painless, bloodless field with increased predictability and instant outcomes. Furthermore, these techniques can help a cosmetic dentist regulate gingiva and osseous outlines with greater creativity in the pursuit of aesthetic dental principles with more efficient use of patient time. Even from the patient standpoint, the reduced requirement for suturing and faster healing times improves case acceptance and enables the increased demand for aesthetic dentistry. The resolution of this paper is to deliver an overview of various laser applications in aesthetic dentistry and its pros and cons over the conventional approaches.
Keywords: photo-stimulation; wavelength; rehabilitation; laser beam; erbium lasers